An Issue of Absolution: Section 391 of the Companies Act - KOH, Pearlie (Institutional Knowledge at Singapore Management University, 2003)
There is an obvious tension in the imposition of directors’ duties. Whilst directors being the management, and therefore the eyes, ears and brain of the corporate person, must be given sufficient discretion to take on entrepreneurial (and hence risky) ventures with a view to profit maximisation, there is also the need to curb excesses, as the potential or opportunity for mismanagement, negligence and fraud is omnipresent. [T]his short article considers section 391 of the Companies Act (Cap 50), arguably the statutory nemesis of directors’ duties. Section 391 gives jurisdiction to the court hearing the case to relieve an officer from liability for negligence, default, breach of duty or breach of trust. This article considers the relieving provision and makes a number of observations about its role and scope.